APPLYING VIDIO-BASED LEARNING AS A TEACHER'S CHALLENGE IN THE SOCIETY 4.0 ERA - Emilia Dahlan; Siti Mayang Sari; Lili Kasmini (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This study aims to explain teachers' challenges in applying video-basedlearning in the era of society 4.0. This research uses descriptive qualitativeresearch methods with the type of research being a literature study. Based onthe research results, it can be seen that video-based learning in the era of society4.0 is a challenge for teachers, especially at the elementary school level. Thesechallenges include limited knowledge about technology and the lack ofsupporting facilities in schools. Another challenge is a change in roles and skillswhere teachers must adapt themselves to become learning facilitators andmaster the use of technology. There are gaps in technology and accessibility,changes in curriculum and learning and changes in evaluation and assessment.